The signaling pathway of hypoxia inducible factor in regulating gut homeostasis - Liu, Wei; Fan, Xueni; Jian, Boshuo; Wen, Dongxu; Wang, Hongzhuang; Liu, Zhenjiang; Li, Bin (Frontiers in Microbiology, 2023)
Hypoxia represent a condition in which an adequate amount of oxygen supply is missing in the body, and it could be caused by a variety of diseases, including gastrointestinal disorders. This review is focused on the role of hypoxia in the maintenance of the gut homeostasis and related treatment of gastrointestinal disorders. The effects of hypoxia on the gut microbiome and its role on the intestinal barrier functionality are also covered, together with the potential role of hypoxia in the development of gastrointestinal disorders, including inflammatory bowel disease and irritable bowel syndrome.Finally, we discussed the potential of hypoxia-targeted interventions as a novel therapeutic approach for gastrointestinal disorders. In this review, we highlighted the importance of hypoxia in the maintenance of the gut homeostasis and the potential implications for the treatment of gastrointestinal disorders.